2023
DOI: 10.3389/fphys.2023.1125931
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of shape-based features ability to predict the ascending aortic aneurysm growth

Abstract: The current guidelines for the ascending aortic aneurysm (AsAA) treatment recommend surgery mainly according to the maximum diameter assessment. This criterion has already proven to be often inefficient in identifying patients at high risk of aneurysm growth and rupture. In this study, we propose a method to compute a set of local shape features that, in addition to the maximum diameter D, are intended to improve the classification performances for the ascending aortic aneurysm growth risk assessment. Apart fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…Journal Pre-proof of the ascending tract. This agrees with the correlation study between local shape features and growth reported in our previous work [42] and with the shape representation provided by the PLS modes.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 92%
See 4 more Smart Citations
“…Journal Pre-proof of the ascending tract. This agrees with the correlation study between local shape features and growth reported in our previous work [42] and with the shape representation provided by the PLS modes.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 92%
“…To increase the likelihood of producing reliable and reproducible results, additional exclusion criteria were set: (1) patients under 25 years of age, (2) aneurysms related to systemic inflammatory diseases, (3) prior aortic valve surgery, (4) acute aortic syndrome, (5) 110 congenital tissue disorders such as Marfan syndrome and (6) images damaged by artefacts. In total, N = 70 patients were included, 50 of whom had already been used in our previous work related to the identification of local shape features [42]. 47 (67.1%) patients had double ECG-gated acquisitions.…”
Section: Dataset 100mentioning
confidence: 99%
See 3 more Smart Citations